(untitled) (Englewood Cliffs, N.J., 1993)
A carefully selected mix of case studies and theoretical articles, this bookranges from classics in philosophy, moral theory, and economics to moderncommentaries by business executives and economists on a host of ethicalissues in business. It includes coverage of relativism, employee rights,morality and corporations, property, and profits and justice ...
Keywords: Đạo đức kinh doanh,Business ethics; Trường hợp nghiên cứu,Case studies